Exchange rate flexibility - Dreyer, Jacob S.; Haberler, Gottfried; Willett, Thomas D.; American Enterprise Institute for Public Policy Research; United States (Washington : American Enterprise Institute for Public Policy Research, 1978)
This book examines the challenges facing the new international monetary system based on flexible exchange rates, multilateral surveillance of exchange rate and balance of payments policies and the management of international liquidity.
"Edited proceedings of the conference ... cosponsored by the American Enterprise Institute and the U.S. Treasury and held ... on April 20-22, 1976."
Includes bibliographical references.
usc 06/06/18
Loans
Keywords: Foreign exchange rates